Performed Laparoscopic Surgery For Gastric Perforation: Case Report - Mirton; Pasihulilzan; Ashan, Hesty Rhauda (CoinReads Media Prima, 2024)
Introduction: Perforated peptic ulcer (PPU) is a life-threatening disease with historically reported high morbidity and mortality rates. The epidemiology of perforated peptic ulcer was appear to be stable in recent. The laparoscopy as primary operation has focused on safety to tread PPU. Case: A 75 years old man presented to our emergency center with generalized abdominal pain since 2 days before admision. Generalize abdominal pain develop suddenly and severe. Patient has history taking NSAID for 7 years to treat pain in the knee joint. He was complaining of chronic and recurrent upper abdominal for 5 year and relieved by food or antacids. He is smoker. After initial resuscitation by adequate administration intravenous lines of fluid and nasogastric tube, Patient underwent a laparocopik surgery, we perform prymari suture and a Graham patch. We followed administration antibiotic and proton pump inhibitor. We perform the suturing to close the perforation site before peritoneal irrigation to avoid the accumulation of infected fluid and other debris. Once irrigation was complete, a large volume of omentum was reinforced above the primary suture site. Conclusion: We successfully managed perforated peptic ulcers with minimally invasive approach. Adequate resuscitation, hypotension in no longer be a significant prognostic indicator. In experienced hand laparoscopic is probably the most appropriate approach for perforated peptic ulcer. Because no upper abdominal incision is made, there I decreased post operative pain and decrease administration of post operative pain medication. The patient rapidly recovers with less complication.